2005
DOI: 10.1016/j.bbamem.2004.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal uptake of nateglinide by an intestinal fluorescein transporter

Abstract: Nateglinide, a novel oral hypoglycemic agent, rapidly reaches its maximum serum concentration after oral administration, suggesting that it is rapidly absorbed in the intestine. However, nateglinide itself is not transported by MCT1 or PEPT1. The aim of this study was to characterize the transporters on the apical side of the small intestine that are responsible for the rapid absorption of nateglinide. It has been reported that the uptake of fluorescein by Caco-2 cells occurs via an H+-driven transporter and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…In this study, we investigated the expression of MCT6 in the human small intestine and compared the transport properties of nateglinide via MCT6 with those previously reported for Caco-2 cells (Okamura et al, 2002;Itagaki et al, 2005a). Our results indicated that MCT6 is located on the apical side of human intestinal villous epithelial cells and mediates the transmembrane transport of nateglinide, suggesting that MCT6 may be involved in the absorption of nateglinide.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In this study, we investigated the expression of MCT6 in the human small intestine and compared the transport properties of nateglinide via MCT6 with those previously reported for Caco-2 cells (Okamura et al, 2002;Itagaki et al, 2005a). Our results indicated that MCT6 is located on the apical side of human intestinal villous epithelial cells and mediates the transmembrane transport of nateglinide, suggesting that MCT6 may be involved in the absorption of nateglinide.…”
Section: Discussionmentioning
confidence: 80%
“…Nateglinide Transport via MCT6 1885 at ASPET Journals on May 12, 2018 dmd.aspetjournals.org been shown to inhibit uptake of nateglinide by Caco-2 cells (Okamura et al, 2002;Itagaki et al, 2005a), did not affect the MCT6-specific uptake of [ 14 C]nateglinide (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…hMCT1, human MCT1. cells, 20) which was identical to the ferulic/H þ cotransport system. 21) Therefore, the transepithelial transport and uptake of fluorescein were measured in Caco-2 cells treated with NaBut or transfected with human MCT1 (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Since we have reported that benzoic acid and salicylic acid significantly inhibited the uptake of nateglinide by Caco-2 cells [19], cis-inhibition studies were performed using benzoic acid and salicylic acid. As shown in Table 1, both of them significantly reduced the uptake of nateglinide.…”
Section: Hydroxyapatite Chromatography Of Intestinal Brush-border Memmentioning
confidence: 99%